Meningkatkan Keterampilan Membaca Permulaan Melalui Penggunaan Media Big-Book Pada Siswa Kelas III Sd Kartika XIII-1 Ambon - Sahetapy, Sarah; Palahidu, Rini; Ririhena, Ribka L. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the level of early reading development using big books. The method used was classroom action research, and the sample consisted of seven third-grade students at Kartika XIII-1 Ambon Elementary School. The results of the study showed that big books can improve early reading skills in Indonesian language learning among third-grade students at SD Kartika XIII-1 Ambon.